Optimizing Screen Time Management for Children’s Devices: Leveraging Token Bucket and Time-Based Algorithms in a Famie Parental Control System (American Journal of Smart Technology and Solutions, 2025)
This study aims to develop a parental control system, Famie, designed to optimize screen time management on children’s devices. The system addresses the growing need for parents to effectively monitor and regulate their children’s screen time in a balanced manner. Integrating the Token Bucket Algorithm and a Time-Based Algorithm enables parents to set flexible screen time schedules and efficiently reset usage time. Famie serves as the parent app, while Famkid functions as the child app. The two apps are connected using a QR code-based pairing system, allowing parents to seamlessly link their devices with their children’s. This connection enables centralized control over screen time and schedule management. The research applies these algorithms to provide a personalized approach to digital parenting, ensuring that children develop responsible screen time habits while maintaining a secure digital environment. Key features include setting screen time schedules via token buckets, where the device remains locked when the bucket is empty and unlocks only when another active bucket becomes available. Additionally, the time-based algorithm serves as a daily reset mechanism, ensuring that buckets are refilled at midnight. Although Android’s security policies impose limitations on device-locking capabilities, the system still offers effective control by focusing on schedule-based access. The results of this study are expected to empower parents in promoting healthier technology habits for their children, benefiting families, researchers, and educational institutions by contributing to the evolving field of algorithm-driven parental control systems.